Psychosocial support during the Ebola outbreak in Kailahun, Sierra Leone. Issue 1 (March 2015) - Garoff, Ferdinand
<x xml:space="preserve">Abstract</x> This field report describes the author's deployment as a psychosocial delegate to the International Federation of Red Cross Ebola epidemic response in Sierra Leone during June and July 2014. He highlights the ongoing impact of an epidemic in a post conflict zone, how addressing fear and stigma is essential in social mobilisation and capacity building efforts, as well as providing empowering messages that give hope and foster collaboration between epidemic responders and community members. Additionally, stress management and adequate supervision are essential for staff and volunteer wellbeing and safety during an Ebola epidemic.